Thermal Compensation Effect of Passage Arrangement Design for Inlet Flow Maldistribution in Multiple-Stream Plate-Fin Heat Exchanger. Issue 15 (14th September 2019) - Peng, Xiang; Qiu, Chan; Li, Jiquan; Jiang, Shaofei
ABSTRACT: Passage arrangement design in fin channels is an efficient methodology for the reduction of the thermal deterioration influence of inlet flow maldistribution in multiple-stream plate-fin heat exchangers. In this work, the thermal compensation effects of passage arrangement design under different statistical parameters of inlet flow maldistribution are investigated. The inlet flow maldistribution in inlet header is analyzed and represented with distribution types, mean, and standard deviation of inlet mass flow rate entering the fin channels. A thermal calculation model based on integer–mean temperature difference method is established, and then, the passage arrangement under inlet flow maldistribution is optimized using a hybrid particle swarm algorithm. The thermal compensation effects for different inlet flow maldistributions and passage arrangements are calculated and compared. The results indicate that the compensation effect of optimization design of passage arrangement increases from 1.1% to 3.9% as the standard deviation of inlet mass flow rate increases from 0.06 kg/s to 0.12 kg/s. The results presented in this study can be used by other researchers to guide the passage arrangement design of actual heat exchanger with inlet flow maldistribution.